Factors associated with walking, moderate and vigorous physical activities in adolescents - Valter Cordeiro Barbosa Filho; Alex Pinheiro Gordia; Teresa Maria Bianchini de Quadros; Evanice Avelino de Souza; Wagner de Campos (Motricidade, 2011)
This study aimed at investigating the relationship between a set of variables (adolescents' gender, age, economic level, nutritional status, and fathers' educational level) and physical activity practices. The sample consisted of 578 students from a public school, aged between 11 and 16 years. The International Physical Activity Questionnaire (IPAQ, version 8, short form) was applied in order to measure their physical activity practices. Chi-square, independent t test and one-way ANOVA were implemented. Thirteen percent of adolescents were physically inactive and no significant difference was found between gender (p > .05). Compared to boys, girls spent more time in walking (p = .019) and vigorous activities (p = .017). Adolescents aged 14-16 years spent more time in walking compared with those aged 11-12 years (p = .026) and 13-year-olds (p = .006). There was a positive association between economic level and time spent in moderate physical activity (p = .034).